Asymmetric Reactions to Work Group Sex Diversity Among Men and Women - Chatman, Jennifer A.; O’Reilly, Charles A. (Academy of Management Journal, 2004)
Attitudes among 178 professional men and women working for a clothing manufacturer and retailer depended on their work groups' sex composition. Findings were consistent with status considerations: women expressed a greater likelihood of leaving homogeneous groups than did men, even though women expressed greater commitment, positive affect, and perceptions of cooperation when they worked in all-female groups. These results suggest that similarity-attraction may be inadequate as the primary theoretical foundation for understanding how work group sex composition influences men and women.